LEGAL REVIEW OF LAND TENURE BY COMMUNITIES ON COASTAL AND COASTAL BOUNDARIES IN PALU CITY AND PARIGI MOUTONG REGENCY - Manga Patila; Dewi Kemala Sari; Abraham Kekka (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2025)
Land acquisition, especially in coastal border areas and coastal areas, has been largely dominated by traditional/customary communities who have lived and inhabited the area for a long time, so that the occupation of land by law for many years has become an assumption for the community as an effort to transfer property rights from the state to them. The formulation of the problem from this study is what is the status of land ownership controlled by the community on the coastal border and coastal areas.? and How to implement the granting of land rights on coastal borders and coastal areas in accordance with applicable laws and regulations. The purpose of this study is to find out the status of land ownership controlled by the community on the coastal and coastal borders. And the implementation of the granting of land rights on coastal borders and coastal areas. This research is empirical research, namely research obtained from experience, observations based on data in the field and information obtained from direct interviews with various sources. Ownership status for communities in coastal areas and coastal borders is a property right obtained from state land and has long been given to local, traditional and customary communities who have lived in the area for less than 20 years and have been making a living or carrying out activities around the coast for generations. The granting of rights to coastal areas is given with Land Rights in the form of Right to Use, namely land rights with a time limit to the community, the implementation of granting land rights in coastal areas and also coastal borders paying attention to the public interest, limited carrying capacity, sustainable development, ecosystem linkage, biodiversity and sustainability of environmental functions.